Exploitation Of Renewable Energies In Achieving Sustainable Development - Case study of Algeria- (Journal of Economic Additions, 2019)
The aim of this study is to highlight the role of renewable energies and their utilization in supporting and achieving sustainable development through its pivotal and effective role in achieving the goals of renewable energies and the potential for the actual production of various renewable energies.  As well as to clarify that Algeria's membership in the Commission on Sustainable Development pushed it to achieve and implement its agenda items. The first step was to exploit renewable energies and harness them to the various potentials for achieving sustainable development.